KEMANDIRIAN BELAJAR SENI BUDAYA SISWA SMP SAAT PANDEMI COVID- 19 - Ni Ketut Suparmi (Pendidikan Seni Drama Tari dan Musik, Universitas Sultan Ageng Tirtayasa, 2021)
Student learning independence is one of the learning characteristics students have. During a pandemic like this, students are required to carry out the learning process from home online. This study aims to determine the level of student learning independence during the Covid-19 pandemic in arts and culture subjects. This research was conducted at SMP Negeri 1 Tanjung, North Lombok Regency with 16 students as respondents. Sampling research using saturated sampling technique. The data collection instrument used was a questionnaire containing 20 statements representing 4 indicators of independent learning, namely self-confidence, responsibility, discipline, and initiative. The research data were analyzed using a Likert scale to determine the level of student learning independence. The results showed that the learning independence of 12 students was in the high category and 4 others were in the very high category. Based on the results of this study, it can be concluded that the learning independence of the students of SMP Negeri 1 Tanjung, North Lombok Regency is still relatively good because they are in the high and very high category even though they have to study online at their respective homes.